ANALISIS KEGIATAN ICE BREAKING UNTUK COPING STRESS SISWA SEKOLAH DASAR - Susilowati, Dwi; Ismiyanti, Yulina; Jupriyanto (Universitas Negeri Medan, 2025)
Academic stress is a common challenge faced by elementary school students, which can negatively impact their emotional well-being and academic achievement. One strategy that can help students cope with stress is ice-breaking activities. This study aims to analyze the role of ice-breaking activities in helping students at SDN Waru manage stress. The research employs a qualitative approach with a case study design. Data were collected through observations and interviews with teachers and students involved in ice-breaking activities. The findings indicate that ice-breaking activities create a more enjoyable learning environment, enhance social interactions, and help students better regulate their emotions. Various activities, such as group games, physical movements, humor or funny stories, breathing exercises, and singing, have been proven effective in reducing stress and increasing students' learning motivation. Therefore, implementing ice-breaking activities in the learning process not only transforms the classroom atmosphere into a more engaging one but also plays a crucial role in supporting students' psychological well-being.